Rigid/flexible polyurethane foam composite boards with addition of functional fillers: acoustics evaluations - C., H. Huang; C., W. Lou; Y., C. Chuang; C., F. Liu; Z., C. Yu; J., H. Lin (Universiti Kebangsaan Malaysia, 2015)
Following rapid technological and industrial development, factories have been equipped with a great deal of machines. The blend of industrial and residential areas in turn resulted in many environmental problems. In particular, machine operation causes noise pollution that easily causes physiological and psychological discomfort for the human body thus makes noise abatement a crucial and urgent issue. In this study, vermiculite functional fillers were added to polyurethane (PU) foam mixtures in order to form sound absorbent PU foams. The correlations between the contents of functional fillers and the sound absorption of flexible and rigid PU foams were then examined. The optimal PU foams were combined with PET/carbon fiber matrices in order to yield the electromagnetic shielding effectiveness. The sound absorption, noise reduction coefficient (NRC), electromagnetic shielding effectiveness and resilience rate of the composite boards were finally evaluated. The test results indicated that rigid PU foam composites can reach a sound absorption coefficient of 0.8 while the flexible PU foam composites have higher mechanical properties.